Cornea verticillata in Fabry disease: a comparative study between slit-lamp examination and in vivo corneal confocal microscopy. Issue 5 (10th August 2019) - Leonardi, Andrea; Carraro, Gianni; Modugno, Rocco Luigi; Rossomando, Valentino; Scalora, Tania; Lazzarini, Daniela; Calò, Lorenzo
Abstract : Purpose: To compare the diagnostic power of slit-lamp examination with the in vivo corneal confocal microscopy (IVCM) as the gold standard in assessing the presence of corneal epithelial deposits in patients with Fabry disease (FD). Methods: Fourteen patients with FD (4 males, 10 females; mean age, 46.8 years) and eight healthy controls (4 males, 4 females; mean age, 36.75 years) were included. All subjects underwent slit-lamp examination and IVCM of both central and peripheral corneal quadrants with the Heidelberg Retina Tomograph-III in combination with the Rostock Cornea Module. Results: In patients with FD, 9 of 28 eyes (32%) showed the presence of cornea verticillata at the slit-lamp examination and 25 eyes (89%) showed the presence of epithelial hyper-reflective deposits at the IVCM. Of the 19 eyes negative at the slit-lamp examination, 16 eyes showed the presence of epithelial deposits at the IVCM. Compared with controls, patients with FD had a significantly reduced number, density and length of nerve fibres at the level of corneal sub-basal nerve plexus, but a significantly higher grade of fibres tortuosity. Conclusions: The slit-lamp examination has a limited diagnostic power in the detection of epithelial deposits in patients with FD when compared with the IVCM. In fact, the slit-lamp examination suffers from a high number of false negative results and, consequently, from a low negative predictive value (16%). IVCM allows the detection of corneal microstructural changes in patients with FD and may represent a reliable tool for the early diagnosis and follow-up of the disease.